Dynamic optimization of tracked vehicle power train based on torsional vibration analysis. (14th May 2016) - Fu, Shengping; Li, Shengbo; Luo, Ning; Elena, Mishchenko
Aiming at the vehicle power train, system dynamic optimization is profoundly studied based on the system torsional vibration characteristics analysis. First, based on the concentrated mass method, the general torsional vibration model of vehicle power train is established and solved after parameters' (inertia, stiffness, and damping) matrix and mathematic constraint conditions are acquired. Furthermore, both free vibration and forced vibration characteristics are analyzed. Second, the effects of the coupling stiffness on the dynamics behaviors of power train are thoroughly analyzed. The sensitivity analysis procedure is explored. And sensitivity models of both free and forced vibration feature parameters are deduced. Finally, dynamic optimization theory model and program are constructed based on genetic algorithm. The optimization results indicate that the proposed optimization method could contribute to the sharp attenuation of system torsional vibration.